The Efficacy of a Novel Microbial 6-Phytase Expressed in Aspergillus oryzae on the Performance and Phosphorus Utilization in Broiler Chickens - Aureli, R.; Faruk , M. Umar; Cechova, I.; Pedersen, P.B.; Elvig-Joergensen, S.G.; Fru, F.; Broz, J. (International Journal of Poultry Science, 2011)
The efficacy and safety of a novel microbial 6-phytase expressed via the use of synthetic genes in Aspergillus oryzae was investigated from d 8 to 22 of age using 480 Ross PM3 broiler chickens. Five treatments were tested. A diet containing 5.6 g/kg of Phosphorus (P) was fed to the control treatment. Another diet containing 4.1 g/kg P was fed to another treatment as negative control. This diet was fed in 3 other treatments with the addition of phytase (500, 1000, or 2000 U/kg). Feed intake, body weight, tibia ash (%) and strength (N) and P and Ca utilization (% of intake) and excretion (g/kg DM) were measured. Enzyme safety was determined by genotoxicity and sub-chronic oral toxicity studies. Lower feed intake and higher weight gain was obtained with the treatment containing 2000 U/kg phytase compared to the two control treatments and the treatment containing 500 U/kg phytase, leading to a significant improvement in FCR with the 2000 U/kg phytase. Tibia strength and ash were improved with the latter and were dose-dependent described by an exponential function. Safety test using a concentrated preparation of the novel 6-phytase enzyme did not reveal any toxicological significant findings. The enzyme did not induce mutagenic activity in the Ames test and did not increase the frequency of micronucleated binucleated cells in the micronucleus assay. In conclusion, this novel microbial 6-phytase improved broiler performance and reduces the need for phosphate fortification of feed. In addition, it can be Generally Recognized as Safe (GRAS) feed ingredient according to the safety test carried out.